RELATIONSHIP WITH SOCIAL SUPPORT THE QUALITY OF LIFE IN PATIENTS PULMONARY TUBERCULOSIS (Studies in Puskesmas Kesamben, Jombang) - Nor Aini; Hindyah Ike; Anita Rahmawati (Jurnal Keperawatan, 2013)
Tuberculosis is one of the infectious disease remains a health problem in the world. Phenomena that occur in society today that so many family members and friends of patients suspected or who have suffered from pulmonary tuberculosis do not want to adjacent and also talk to the patient. It would be highly offensive to people. This will have an impact on the psychological condition of patients with TB. All of these things will affect the success of treatment and then further degrade the quality of life of patients. This study aims to analyze the relationship of social support and quality of life in patients with pulmonary tuberculosis. This study used cross sectional analytic method. The population was 33 patients suffering from pulmonary tuberculosis in Puskesmas Jombang Kesamben and sample using simple random sampling with 30 respondents. The variables of this study was the independent variable and the dependent variable social support quality of life. Data processing using the editing, coding, scoring and tabulating. The relation between those two variables used test of “Spearman Rank” with an error level 5%. The research results were relation social support with quality of life in patients with Pulmonary tuberculosis in Puskesmas Kesamben. The writer found the medium social support was total 15 respondence (50%) while, many part from respondence belong to medium quality of live was total 16 respondence (53,4%). Based on the results of this study concluded that there was a relationship social support with quality of life in patients with pulmonary tuberculosis in Puskesmas Kesamben, Jombang p>0,05.